"Gekneld in de marge" : een actualisatie van het zwartboek "Knelpunt" - Martens, Luc; Vandenhoeck, Erik; Vanderslycke, Didier (Antwerpen: Uit de Marge, 1987)
"Tekstsamenstelling: Luc Martens, Erik Vandenhoeck, Didier Vanderslycke"